Penerapan The Four-Quadrant Model of Facilitated Learning (4QM) terhadap Perkembangan Kemampuan Membaca Anak Berkebutuhan Khusus - Stefanie, Stefanie; Prasetyaningsih, Roh Hastuti (Jurnal Terapi Wicara dan Bahasa, 2024)
Background: Childreni withi speciali needsi (ABK)i arei individualsi withi uniquei characteristicsi thati differi fromi typicali children,i exhibitingi mental,i emotional,i ori physicali developmenti thati isi noti ini linei withi theiri chronologicali age.i ABKi ofteni facei learningi difficulties,i particularlyi ini reading.i Objectives:i Toi determinei thei effecti ofi thei Four-Quadranti Modeli ofi Facilitatedi Learningi (4QM)i interventioni oni thei readingi developmenti ofi childreni withi speciali needs.i Thei interventioni involvedi ai readingi developmenti programi conductedi ati thei Callingi Stari Childi Developmenti Centeri ini Balikpapan,i Easti Kalimantan,i overi twoi months.i Methods:i Thisi studyi employedi ai pre-experimentali designi withi ai one-groupi pretest-posttesti approach.i Thei populationi comprised children with special needs diagnosed with ASD, ADHD, ADD, and dyslexia, aged 7–10 years, enrolled at the Calling Star Child Development Center in Balikpapan, East Kalimantan. A total sampling technique was used, involving 10 children with special needs (9 boys and 1 girl). Data analysis was conducted using a parametric statistical method, specifically the Paired T-Test, through SPSS version 25.0. Results: The study revealed a p-value of 0.000 (p < 0.05) with a mean pretest-posttest score difference of 12.7, indicating a statistically significant improvement in reading skills before and after the 4QM intervention. Among the diagnoses, children with ASD exhibited the greatest improvement in reading skills following the 4QM intervention, compared to those with ADD, ADHD, and dyslexia. Conclusion: The implementation of the Four-Quadranti Modeli ofi Facilitatedi Learningi (4QM)i significantlyi influencesi thei readingi developmenti ofi childreni withi special needs. Keywords: reading, ABK, dyslexia, WCPM, 4QM